Edukasi terhadap Mahasiswa Keperawatan Mengenai Pengembangan Kepribadian di Unit Gawat Darurat Melalui Media Video (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Personality development is a fundamental aspect in the formation of nursing students as prospective professional nurses, especially in services in the Emergency Unit (ER). The personality of nurses in the ER is reflected in the ability to think critically, effectively communicate, caring attitudes, and professional performance that supports the quality of service. This community service activity aims to increase the knowledge of nursing students about personality development in the ER through educational video media. The method used is health education with a pre-test and post-test design involving 19 nursing students. The results of the activity showed an increase in the average score of student knowledge from 14.58 in the pre-test to 19.16 in the post-test. These findings indicate that educational video media is effective in increasing students' understanding of the role of critical thinking, communication, caring, and performance in the ER. In addition, this activity also contributes to strengthening student readiness to face the challenges of clinical practice in an emergency environment. Thus, the use of video media as an educational means can be an innovative strategy in supporting the personality development of nursing students, as well as strengthening the professional competencies needed in emergency health services.